Enhancement of Trk Signaling Pathways by the Cholestane Amide Conjugate MCC-257 - Maki K. Yamada; Yoshiyuki Konishi; Bunpei Kakinoki; Koji Ikegami; Mitsutoshi Setou (Elsevier, 2008)
The cholestane amide conjugate MCC-257 has been shown to augment the effects of nerve growth factor (NGF) on cell survival and on tyrosine phosphorylation of the TrkA receptor in PC12 cells. Recent findings suggest that signaling pathways downstream of Trk are regulated independently. We describe here our finding that the NGF-induced phosphorylation of both ERK and Akt are accelerated by MCC-257. Analysis of the common features of the augmented pathways suggests that TrkA is most likely to be the primary target of MCC-257 and that both ERK and Akt may be involved in the cellular effects of this compound. Keywords:: lipid, neurotrophin, survival